Konstruksi Judicial Order dalam Putusan Mahkamah Konstitusi - Siti Partiah (Fakultas Syariah IAIN Madura, 2021)
The decision of the Constitutional Court is a legal product produced by the Court, whose decision is final and binding. The meaning of the final and binding clause means that since the decision is read in front of the court it is open to the public, has binding legal force and there is no further legal action. This research includes normative juridical research, using a statutory approach and a conceptual approach. Juridically the authority of the judicial order is implied in Articles 10 and 23 of Law no. 15 of 2019 amendments to Law no. 12 of 2011 concerning the Establishment of Legislation, and is explained again in DPR Regulation No. 13 of 2016 concerning procedures for drafting a national legislation program. The construction of the judicial order lies in the final and binding nature of the Constitutional Court's decision itself. Follow-up actions are not always delegated to the legislature, because in practice it is permissible for relevant institutions that have the authority to issue orders or regulations so that there is no legal vacuum for too long and does not interfere with the running of the government.